OBTAINING AND RESEARCH OF THE SUPRAMOLECULAR COMPLEXES OF ALKALOID SALSOLINE WITH CYCLODEXTRINS BY NMR SPECTROSCOPY - Nurkenov Oralgazy Aktayevich; Seilkhanov Tulegen Muratovich; Fazylov Serik Drakhmetovich; Issayeva Ayaulym Zhanabekovna; Seilkhanov Olzhas Tulegenovich; Zhaksybayeva Gulnar Shaikhidenovna (Academic Scientific Journal of Chemistry, 2019)
One-dimensional NMR 1 H, 13C and DEPT and two-dimensional spectroscopy COSY (1 H-1 H), 1 H-1 H TOCSY, 1 H-1 H ROESY, HMQC (1 H-13C) and 1 H-13C HMBC were used to study the alkaloid salsoline, as well as its supramolecular components, and the supramolecular components of the HMBC spectroscopy polysaccharides α- and γ-cyclodextrins. Schemes of proton correlation with protons through three carbon atoms (1 H-1 H) and HMQC (1 H- 13C) in the initial state of the alkaloid under study. The use of the possibilities of two-dimensional spectroscopy COSY (1 H-1 H), 1 H-1 H TOCSY, 1 H-1 H ROESY, HMQC (1 H-13C) and 1 H-13C HMBC when studying the alkaloid under study correctly and uniquely identify the structure of the substrate of supramolecular self-assembly with cyclic fields. Homonuclear and heteronuclear correlation NMR COSY (1 H-1 H) and HMQC (1 H-13C) are also used to confirm the structure and structure of the cyclic polysaccharides of α- and γ-cyclodextrins. The chemical shifts of the aliphatic and hydroxyl protons of the inner and outer surfaces of the receptors were determined. A comparative analysis of the 1 H and 13C NMR spectra of salsoline, α- and γ-cyclodextrins and their supramolecular complexes was carried out. Certain changes have the chemical shifts of 1 H and 13C nucleus of salsoline, as well as α- and γcyclodextrins in supramolecular complexes. The proton integral intensities of the substrate and receptors in the 1 H NMR spectra were definitely that the supramolecular self-assembly with alpha and γ-cyclodecrins occurs with the formation of complexes without including (external) due to the intermolecular interaction of hydroxyl groups from both the alkaloids and cyclodextrins . The water-soluble aggregates formed during this process are capable of solubilizing the required substrate through non-inclusive complexation.